Economic gains of improving soil fertility and water holding capacity with clay application: the impact of soil remediation research in northeast Thailand - Saleth, Rathinasamy Maria; Inocencio, Arlene B.; Noble, A.D.; Ruaysoongnern, Sawaeng (Informa UK Limited, 2009)
Using survey data collected from 250 farmers, this paper evaluates the impact of the Soil Remediation Research Project (SRRP) undertaken by International Water Management Institute (IWMI) in Northeast Thailand during 2002-2005. SRRP has demonstrated and promoted the application of clay as a quick and low-cost means for improving the fertility and water holding capacity of sandy soils. The impact evaluation suggests that the SRRP has a net present value (NPV) of US$0.7 million with a benefit-cost ratio (BCR) of 3.1 for the sample context and an NPVof US$99.5 million with a BCR of 317.7 for the larger context of the region.